Prevalence and risk factors associated with Chlamydia trachomatis, Neisseria gonorrhoeae, and Mycoplasma genitalium among women in Pelotas, Southern Brazil. (April 2020) - Silveira, MF; Bruni, MP; Stauffert, D; Golparian, D; Unemo, M
The frequently asymptomatic sexually transmitted infections (STIs) caused by Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Mycoplasma genitalium (MG) are poorly diagnosed in Brazil and can lead to severe complications/sequelae without timely detection and treatment. We investigated prevalence of CT, NG, and MG infections and associated demographic, behavioral, and clinical factors in consecutive women attending a gynecology and obstetrics outpatient clinic in Pelotas, Southern Brazil. Vaginal swab samples were prospectively obtained from asymptomatic and symptomatic women (n = 498) from August 2015 to December 2016 and tested with Aptima Combo2 and Aptima M. genitalium assays (Hologic). The prevalence of CT, NG, and MG was 6.8% (34/498), 1.0% (5/498), and 4.2% (21/498), respectively. Three (0.6%) cases of CT and NG co-infection and one (0.2%) case of CT and MG co-infection were identified. The risk factors associated with these bacterial STIs were youth (<30 years), no steady sexual partner, infection with additional STI, and lack of income. Bacterial STIs, particularly CT and MG, were prevalent among women, including pregnant women (60% of positive cases), in Pelotas, Brazil. Sensitive and specific diagnostic testing and early treatment are essential to control STIs, limit transmission chains, avoid future complications/sequelae, and reduce health and cost burdens on the population.